2019
DOI: 10.3390/biom9040127
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Lung Cancer, and Anti-Bacterial Activities of Toxicodendron vernicifluum

Abstract: This work tested antioxidant, anti-lung cancer, and antibacterial activities by in vitro, in vivo, and computational experiments for the metabolites extracted from the bark, seed, and stem of Toxicodendron vernicifluum. The results showed that all the extracts significantly scavenged 1,2-diphenyl-1-picrylhydrazyl (DPPH) in a dose-dependent manner. But, the total phenol content (TPC) ranged from 2.12 to 89.25% and total flavonoids content (TFC) ranged from 1.02 to 15.62% in the extracts. The methanolic bark ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…e CJS-EO investigated in this study was primarily composed of hexamethylcyclotrisiloxane, which constituted 42.36% of the total chemical content. Toxicodendron vernicifluum containing hexamethylcyclotrisiloxane has been shown to exhibit various biological and pharmacological activities, including central, antimicrobial, and antitumor activities [37]. In our study, high concentrations of CJS-EO indicated only slight cytotoxic effects on melanocytes.…”
Section: Discussionmentioning
confidence: 42%
“…e CJS-EO investigated in this study was primarily composed of hexamethylcyclotrisiloxane, which constituted 42.36% of the total chemical content. Toxicodendron vernicifluum containing hexamethylcyclotrisiloxane has been shown to exhibit various biological and pharmacological activities, including central, antimicrobial, and antitumor activities [37]. In our study, high concentrations of CJS-EO indicated only slight cytotoxic effects on melanocytes.…”
Section: Discussionmentioning
confidence: 42%
“…The presence of various compounds in hexane extracts of GM, YM, CC, and RB could also contribute synergistically to the inhibition of protein expression in bacterial cells leading to cell death. Recently, DNA gyrase inhibitor, novel bacteria topoisomerase inhibitors (NBTIs) has been discovered as potential target together with bacterial protein topoisomerases II and IV for inhibiting bacteria growth and developing novel antibacterial agents (Franco‐Ulloa et al., 2018; Saravanakumar et al., 2019). This work showed the antibacterial potency of di‐tert‐butylbenzene, cyclododecane, and 3,5‐dimethylbenzaldehyde from cereals and their by‐products.…”
Section: Resultsmentioning
confidence: 99%
“…Computer‐based molecular docking method was performed to identify the main compounds responsible for the antibacterial activity of hexane extracts of GM, YM, CC, and RB samples based on their possible binding mode and theoretical affinity toward four chained structured binding protein of bacterial type II topoisomerase (4PLB) and Lipoprotein X complex (LpxC)‐ UDP‐3‐O‐(R‐3‐hydroxymyristoyl)‐N‐acetylglucosamine deacetylase. Molecular interactions between the extract compounds (ligands) and targeted protein (receptor) and their molecular docking score (Kcal/mol) were analyzed using Argus Lab 4.0.1 (Mark Thompson and Planaria Software LLC) and BIOVIA Discovery studio 2016 (Accelrys Software Inc., San Diego, CA, USA) (Saravanakumar et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Toxicodendron vernicifluum Stokes (TVS) was found to contain a number of bioactive phytochemicals, including alkaloids, polyphenols and flavonoids [12]. Previous research has shown that TVS extract has antioxidant, anti-bacterial, anti-obesity, anti-proliferative, anti-inflammatory, and anti-tumor effects [12][13][14][15][16][17][18][19][20][21][22]. Despite the beneficial pharmacological effects of TVS, its use has been somewhat limited due to the presence of urushiol an allergenic substance, that is a mixture of several derivatives of catechol.…”
Section: Introductionmentioning
confidence: 99%